Financial literacy and SME firm performance - Eniola, Anthony A.; Harry, Entebang; Ley, Kyra Sy Law (International Journal of Research Studies in Management, 2016)
The performance of the SME firm was viewed along the full proportions of financial, strategic and structural development. The socioeconomic function performed by SMEs is widely known in developing and emerging countries. But, in recent times, developing and developed nations have become more and more concerned about the level of financial literacy of the entrepreneur. This has emanated from peculiar to declining public and private to support systems and wide-ranging developments in the financial marketplace. Concern was also intensified by the challenging faced by the SME firm in financial context aided by the recognition that dearth of financial literacy has been one of the many elements responsible for lacks proper knowledge or information about financial decision making and that these decisions could, in turn, have tremendous unexpected consequences. Subsequently, financial literacy is now globally recognized as a major factor of economic and financial stability and development of SMEs for performance. A series of tangible trends underpin the growing worldwide interest in financial literacy as a major life skill, thus, this study set to review the influence of financial literacy on the performance of the SMEs from Nigeria’s context. The study will serve as an information because that will promote and orient SMEs firm performance towards financial awareness, knowledge and perceive attitude. Also, the applied significant framework developed will assist SMEs firm owners and policy makers to identify the importance of financial literacy.